Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds